Effects of Pore Size and Crosslinking Methods on the Immobilization of Myoglobin in SBA-15 - Miao, Hengmin; Li, Maosheng; Sun, Xiaochun; Xia, Jikun; Li, Yanqing; Li, Jiao; Wang, Fang; Xu, Jiakun (Frontiers in Bioengineering and Biotechnology, 2022)
A series of stable mesoporous silica sieves (SBA-15) with different pore sizes (9.8, 7.2, and 5.5 nm) were synthesized using a hydro-thermal method. The resulting mesoporous material was then utilized for protein immobilization using myoglobin (Mb) as the target protein. The effects of pore size and adsorption methods on the immobilization efficiency of Mb in a mesoporous material were studied. The SBA-15 with a pore size 7.2 nm showed the best loading capacity, reaching 413.8 mg/g. The SBA-15 with a pore size of 9.8 nm showed the highest retained catalytic ability (92.36%). The immobilized enzyme was more stable than the free enzyme. After seven consecutive assay cycles, Mb adsorbed by SBA-15 (Mb/SBA-15) and Mb adsorbed by SBA-15 and crosslinked with glutaraldehyde (Mb/G/SBA-15) retained 36.41% and 62.37% of their initial activity, respectively.